2016
DOI: 10.1037/pro0000094
|View full text |Cite
|
Sign up to set email alerts
|

Exposure therapy practices and mechanism endorsement: A survey of specialty clinicians.

Abstract: Studies have suggested that exposure is a key ingredient in the treatment of youth with anxiety disorders and obsessive–compulsive disorder (OCD), yet there are several barriers to the implementation of exposures. This may reflect the lack of detail in treatment protocols specifically outlining the delivery of exposure and the lack of consensus on treatment mechanism. The aim of this study was to learn how experts treating this population practice exposure treatment and conceptualize treatment mechanism on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 52 publications
0
16
0
1
Order By: Relevance
“…Clinician's understanding of the mechanisms of change underlying ET was assessed using a 9-item questionnaire developed for this study. This extended research by Stewart et al (2016) which was based on a single question. A review of the literature revealed conceptual differences in the theoretical underpinnings of ET based on the habituation, cognitive, and inhibitory learning models, which also guide the application of various treatment components (Abramowitz et al, 2012;Clark & Beck, 2010;Craske et al, 2012Craske et al, , 2014.…”
Section: Theoretical Orientationmentioning
confidence: 90%
See 1 more Smart Citation
“…Clinician's understanding of the mechanisms of change underlying ET was assessed using a 9-item questionnaire developed for this study. This extended research by Stewart et al (2016) which was based on a single question. A review of the literature revealed conceptual differences in the theoretical underpinnings of ET based on the habituation, cognitive, and inhibitory learning models, which also guide the application of various treatment components (Abramowitz et al, 2012;Clark & Beck, 2010;Craske et al, 2012Craske et al, , 2014.…”
Section: Theoretical Orientationmentioning
confidence: 90%
“…Participants were also asked whether they used CBT and how often they used ET to treat ADs or OCD. Further, participants were asked how often they provide exposure according to the following description adapted from Stewart et al (2016): ‘ For the purpose of this study exposure therapy is defined as a therapeutic technique that involves having a client confront feared objects or situations (places, objects, outcomes, thoughts, feelings, sensations, or memories) ’.…”
Section: Methodsmentioning
confidence: 99%
“…Coping Cat (21)) sadrže različite druge komponente (npr. kognitivno restrukturiranje, relaksacija), značajnija poboljšanja primjećuju se tek nakon uvođenja izlaganja (22).…”
Section: Introductionunclassified
“…Coping Cat (21)) contain various other components (e.g. cognitive restructuring, relaxation), significant improvement is noticed only after introducing exposure (22). Clinical experience indicated a relatively high percentage of anxious patients who do not react to treatment (34-36%), as well as high treatment dropout rates (16-20%).…”
Section: Introductionmentioning
confidence: 99%
“…Imagination in psychotherapy treatment could involve the patients' capacity to imagine new or different outcomes, envision getting better, or engage in particular interventions that include visualizations (e.g., imaginary exposures, autogenic training for biofeedback, and virtual reality). Indeed, in the initial stages of exposure therapy, which has been shown to be effective for reducing the symptoms of a number of anxiety disorders, patients are asked to engage in imaginary exposures concerning the source of their anxiety (Stewart et al, 2016). Furthermore, imagining worrisome events in more (compared to fewer) detail results in lower levels of worry, and increased subjective probability of a good outcome (Brown, MacLeod, Tata, & Goddard, 2002;Jing, Madore, & Schacter, 2016).…”
mentioning
confidence: 99%